Metaverse for smart cities: A survey - Zefeng Chen; Wensheng Gan; Jiayang Wu; Hong Lin; Chien-Ming Chen (Internet of Things and Cyber-Physical Systems)
The concept of a smart city is geared towards enhancing convenience and the efficient management of city areas through innovation. As Metaverse rises in the 2020s, providing the possible direction for a new generation of the Internet, it has a huge number of opportunities to promote smart cities. The Metaverse can empower smart cities in various aspects. In this article, we provide a detailed review of smart cities based on Metaverse technologies. Firstly, we introduce the Metaverse and smart cities and describe the future vision and applications of smart cities, which are based on the Metaverse. In addition, we discuss the essential technologies for smart cities in the Metaverse and the currently available solutions. Additionally, we have some concerns regarding the potential of Metaverse and there are still unresolved issues that should be addressed. The purpose of this article is to provide researchers and developers with essential guidance and opportunities to propel the development of the Metaverse and smart cities.